Analysis of Radiant Gamma Illumination Effects on Pancreatic Insulin Levels Before and After The Administration of Pare Fruit Extract (M. charantia) On Weed Mice Glucose - Zulkarnain Zulkarnain; Johan A. E. Noor; Unggul P Juswono (Natural B, Journal of Health and Environmental Sciences, 2013)
Gamma rays are ionizing radiation causes cells damage. Cells damage was caused by radiation related to free radicals as a product when the interaction was happened. The cell defense mechanisms against free radicals involves an active compound called antioxidant that can neutralize it. The objectives of this research were to analyze effects of gamma radiation and to investigate the effects of M. charantia extract giving on the pancreas resistance in producing insulin. One hundred eighty mice were used in this research. They were divided into four group: negatif control (K-), radiation non-extract (R-), positif control (K+) and radiation with extract (R+). The Mice were treated with 200 mg/kg BB, 400 mg/kg BB, 600 mg/kg BB, 800 mg/kg BB, and 1000 mg/kg BB. Exposure of gamma rays is given fractionally for five days with 100 rad per fraction ranging from 100 rad, 200 rad, 300 rad, 400 rad and 500 rad per treatment. Insulin levels was measured by ELISA. The results showed that radiation exposure reduced the insulin levels, increase in radiation dose causes increasing of reduction of insulin levels. The giving of M. charantia extract reduced of reduction of insulin levels and also maintained the insulin levels.